One-Pot Synthesis of Chloromethylated Mesoporous Silica Nanoparticles as Multifunctional Fillers in Hybrid Anion Exchange Membranes - He, Xueyi; Gang, Mingyue; He, Guangwei; Yin, Yongheng; Cao, Li; Wu, Hong; Jiang, Zhongyi (Chinese journal of chemistry, 2017)
Chloromethylated mesoporous silica nanoparticles （CM MSN） were synthesized through co-condensation of tetraethoxysilane and （chloro） phenyltrimethoxysilane precursors using hexadecyl trimethyl ammonium bromide as template.With the addition of the particles into chloromethylated poly （ether ether ketone） （PEEK）,the hybrid membranes were prepared by a solution-casting method after complete quatemization of the casting solution.The successful synthesis of the particles was verified by transmission electron microscopy,X-ray diffraction and Fourier transform infrared spectroscopy while the effect of CM MSN incorporation on membrane performance including thermal stability,mechanical strength and hydroxide conductivity was investigated by thermal gravimetric analysis,electronic stretching machine,alternating-current impedance and so on.Owing to the large pore volume and high surface area of the particles,the hybrid membranes exhibited enhanced hydroxide conductivity （88.7% increase at 60 ℃,100% RH with 5.0 wt% filling content） due to an increase in ion concentration and optimization of the channel morphology.Besides,higher mechanical strength,thermal and dimensional stability of hybrid membranes were obtained compared with those of the imidazolium PEEK membrane.